Partnerships for improved food safety: MESPT's engagements in effective pesticides governance and management in selected counties in Kenya - Akidiva, Alex; Nyangori, Godfrey; Kinoti, Doreen; Amukhoye, Rebecca (Frontiers in Sustainable Food Systems, 2024)
Pesticides continue to receive criticism due to their adverse impacts on the environment and human health, a food safety concern emanating from pesticide residues in food and the occupational pesticide exposure risks on farms. This usage has elicited increased attention from policymakers, consumer organizations, and the private and public sectors, pushing the authorities to strengthen pesticide governance and compliance. For instance, the East Africa Community (EAC) has borrowed heavily from the United States and European Union in revising its pesticide standards, which are currently under adoption among the six member states. The Pest Control Products Board (PCPB) in Kenya is at the frontline in the domestication and adoption of the EAC standards by developing new bills and reviewing regulations guiding pesticide usage. Furthermore, with agriculture being a devolved function, counties have woken up and are exploring avenues for promoting the wise use of pesticides. Counties are leveraging partnerships and multi-stakeholder collaboration to efficiently strengthen the pesticide policy-practice nexus. Micro Enterprises Support Program Trust (MESPT), a development organization in Kenya, is closely partnering with and building the capacity of 21 county governments to improve food safety and increase sustainable agricultural productivity through good agricultural practices (GAP) initiatives. This paper reviews the deliberate programmatic interventions by MESPT in facilitating investments within food safety control systems by key sector players. Furthermore, the paper highlights institutional efforts to strengthen farmer organizations to comply with and adapt sustainable agricultural practices that promote the reduced and safe use of pesticides in production. Through MESPT interventions, County Governments have established a functional food safety coordination mechanism and surveillance system backed by legal infrastructure. Additionally, the private sector has been capacitated on food safety compliance, thus influencing smallholder farmers to meet market standards, especially for formal markets. Across the counties, multi-stakeholder collaborations have been strengthened, fueling timely discussions on pesticide compliance toward improved food safety.